Meningkatkan Perkembangan Kognitif Anak Melalui Pemanfaatan Media Looseparts Berbasis STEAM di Raudhlatul Athfal - Amala, Nisael (Allimna: Jurnal Pendidikan Profesi Guru, 2023)
The purpose of this study was to obtain information about the application of STEAM-based looseparts media and the extent of its influence on the cognitive development of children aged 5-6 years in group B at RA AL-Hikmah Turus, Gampengrejo District, Kediri Regency. The method used is classroom action research which is one of the efforts to improve learning to be of higher quality and as evidence that educators can present learning in a more professional manner. The research background was carried out at RA AL-Hikmah Turus, Gampengrejo District, Kediri Regency in November 2022. The subjects of this study were 18 children of group B2 RA AL-Hikmah Turus Gampengrejo for the 2022/2023 school year. Data obtained using data collection techniques such as interviews, observation, and documentation. From the results of the study it can be concluded that learning that utilizes loose parts media with STEAM media is able to increase the cognitive development of group B children gradually from pre-cycle, cycle I to cycle II. Through the research that has been carried out, there are several suggestions that the author gives to: 1) Teachers, to implement learning using STEAM-based loose parts media to improve children's cognitive; 2) Institutions are expected to be able to facilitate learning with loose parts media from various types of objects; 3) Future researchers, to be able to examine the use of loose parts for learning in various aspects of child development.